Effects of Varied Surgical Simulation Training Schedules on Motor-Skill Acquisition. (February 2020) - Ritter, Frank E.; Yeh, Martin K.-C.; Yan, Yu; Siu, Ka-Chun; Oleynikov, Dmitry
There have been many studies to evaluate the effect of training schedules on retention; however, these usually compare only 2 drastically different schedules, massed and distributed, and they have tended to look at declarative knowledge tasks. This study examined learning on a laparoscopic surgery simulator using a set of procedural or perceptual-motor tasks with some declarative elements. The study used distributed, massed, and 2 hybrid-training schedules that are neither distributed nor massed. To evaluate the training schedules, 23 participants with no previous laparoscopic experience were recruited and randomly assigned to 1 of the 4 training schedules. They performed 3 laparoscopic training tasks in eight 30-minute learning sessions. We compared how task time decreased with each schedule in a between-participants design. We found participants in all groups demonstrated a decrease in task completion time as the number of training sessions increased; however, there were no statistically significant differences in participants' improvement on task completion time between the 4 different training schedule groups, which suggested that time on task is more important for learning these tasks than the training schedule.